Health and Literacy: Supporting the Oral Health Research Agenda - Rima E. Rudd, MSPH, ScD; Alice M. Horowitz, PhD (Blackwell Synergy, 2005)
As is noted in Healthy People 2010,good oral health can be achieved and enjoyed by all through the application of known preventive regimens and routine dental visits (1).